PENDIDIKAN ANTIKORUPSI SEBAGAI INVESTASI JANGKA PANJANG DALAM UPAYA MEWUJUDKAN TUJUAN NASIONAL - Made Mita Antari (Universitas Pendidikan Ganesha, 2022)
Corruption has been a biggest threats to the survival of the state and national. Corruption can be said as a problem of a country that has mushroomed in various countries including Indonesia. The complexity of the problems and the negative impact of corruption are of course very threatening to the stability of the country in an effort to achieve the nation's national goals. If this is not handled through preventive and repressive efforts then corruption will destroy the integrity NKRI. Thus it is necessary to make efforts through anti-corruption education as a investment in order to realize national goals for all Indonesian people. With anti-corruption education, the culture and character of the nation will also be formed which has anti-corruption values. Given the importance of this matter, strong synergies from all national elements are needed in order to suppress corruption cases and foster anti-corruption character through anti-corruption education. This article used library research method for data collection. This article used case approach with empirical research.